On-DNA Cross-Dehydrogenative Coupling Reaction toward the Synthesis of Focused DNA-Encoded Tetrahydroisoquinoline Libraries - Wen, Xin; Duan, Zhiqiang; Liu, Jiaxiang; Lu, Weiwei; Lu, Xiaojie (Organic letters, 2020)
To expand the chemical space of DNA-encoded library (DEL) technology, we have developed the DNA-compatible cross-dehydrogenative coupling reaction between tetrahydroisoquinolines (THIQs) and a series of nucleophiles such as nitromethane, terminal alkynes, and so on. Both photo- and metal-promoted conditions have been successfully established for this C-1 derivation of THIQs, as exemplified by the addition of nitromethane. All of these new DNA-compatible transformations have paved the way for the divergent oriented synthesis of THIQ-focused DELs.